Representation of Intercultural Communication in Minari Film (Analysis Semiotics Charles Sanders Pierce): Representation of Intercultural Communication (Analysis Semiotics Charles Sanders Pierce) - Asnur, Sardian Maharani; Rauf, Masykur; Junaid, Syahruni; Yunita, Silfa; Asmida, (Journal of Islamic Culture and Literature (JICeL), 2023)
Abstract This study discusses intercultural communication in Minari Film which aims to know and collect signs related to Intercultural Communication in the film "MINARI". In this study, we made the MINARI Film as the main object in the research by considering the storyline and impression messages contained in the film which is dominated by cultural and other values This research is focused on To study intercultural communication in the film "Minari" Semiotics is a science or method of analysis to study signs. Signs are devices used in trying to find a way in this world, among humans and with humans.The author uses Charles Sanders Peirce's semiotic analysis. . In general, Semiotics is the study of signs in human life. Semiotics can be classified into two, namely structural semiotics and pragmatic semiotics (Hoed, 2011: 28). In Peirce's semiotics, icons, indices and symbols are key to his analysis (Fiske, 2012: 80). The author uses this method to represent intercultural communication. Research data through qualitative methods and processed descriptively. Researchers use film as an instrument to find out more valid data. This research was conducted to increase and expand the knowledge of readers about intercultural communication in a film. Based on the results of research that the author did on the film "Minari" using Charles Sanders Preice semiotica analysis. We can see that the film uses various signs to communicate cultural differences and challenges faced by Korean immigrant families. This Minari film uses various signs such as sequences, scenes, dialogues and shots to analyze the meaning in the film. The author concludes that the results of the signs used in the film reveal the tolerance and intermingling of the two cultures due to long-term communication which is intercultural communication. Keywords: Representation, Intercultural, Minari Film